SELF-MANAGEMENT - Anton PRETORIUS (Social Sciences and Education Research Review)
This paper investigates the importance of the emotional intelligence skill of self-management for secondary school principals. The study used a phenomenological design within a qualitative research approach which included four secondary schools. A total of four principals and 19 teachers participated. The findings revealed that self-management as an emotional intelligence skill may be a deciding factor in the quality of principals’ leadership and management practices at school. Four self-management sub-skills—emotional regulation, optimism, adaptability and stress-management—seemed beneficial for principals. It is recommended that principals consider and allocate time for self-development regarding these skills.